Guest of a Sinner : A Novel - Wilcox, James (Book collections on Project MUSE., 2004)
"It is 22 cats that drive the dazzlingly handsome Eric Thorsen to distraction and into the apartment-if not immediately the arms-of Wanda Skopinski, the rather mousy woman he meets at church when she thrusts a lesbian romance novel upon him. The stench from downstairs drives him from both his rent-controlled apartment and his complacency as a not-quite-successful piano teacher. In his sixth novel, James Wilcox moves beyond the modern South he has etched so vividly and amusingly in the past to take on Manhattan. But somehow he manages to bring the city down to size. ... The book is filled wit